Positive and Negative Experiences on Social Media and Perceived Social Isolation. Issue 6 (July 2019) - Primack, Brian A.; Karim, Sabrina A.; Shensa, Ariel; Bowman, Nicholas; Knight, Jennifer; Sidani, Jaime E.
Purpose: To examine the association between positive and negative experiences on social media (SM) and perceived social isolation (PSI). Design: Cross-sectional survey. Setting: One large mid-Atlantic University. Participants: A total of 1178 students aged 18 to 30 were recruited in August 2016. Measures: Participants completed an online survey assessing SM use and PSI. We assessed positive and negative experiences on SM by directly asking participants to estimate what percentage of their SM experiences involved positive and negative experiences, respectively. Social isolation was measured using the established Patient-Reported Outcomes Measures Information System scale. Analysis: We used multivariable logistic regression to assess associations between both positive and negative experiences on SM and PSI. Primary models controlled for sex, age, race/ethnicity, educational status, relationship status, and living situation. Results: Participants had an average age of 20.9 (standard deviation = 2.9) and were 62% female. Just over one-quarter (28%) were nonwhite. After controlling for all sociodemographic covariates, each 10% increase in positive experiences was not significantly associated with social isolation (adjusted odds ratio [AOR] = 0.97; 95% confidence interval [CI]: 0.93-1.005). However, each 10% increase in negative experiences was associated with a 13% increase in odds of PSI (AOR = 1.13; 95% CI: 1.05-1.21). Conclusion: Having positive experiences on SM is not associated with lower social isolation, whereas having negative experiences on SM is associated with higher social isolation. These findings are consistent with the concept of negativity bias, which suggests that humans tend to give greater weight to negative entities compared with positive ones.